PEDAGOGICAL CONDITIONS OF EDUCATION OF ADOLESCENTS’ MEANINGFUL LIFE VALUES IN FAMILY - Zhurba, Kateryna; Dokukina, Olena (Theoretical and Methodical Problems of Children and Youth Education, 2021)
The article deals with education of the adolescents’ meaningful life values in family. The concept of «meaningful life values» is defined as a system of generalized aspirations related to the person’s life, which in a developed form characterizes one’s spiritual and moral self-concept, self-search and appropriate lifestyle expressed in person’s behaviour, activities and communication. It is found out that meaningful life values are freedom, love, dignity and tolerance. It is determined that meaningful life values are a fundamental characteristic of human existence, which determines a person’s ability to choose his or her being, to manage it, to feel independent and, at the same time, responsible for the results of activities. Love as a person’s highly sensual attitude towards people, to oneself that stimulates the development of personality’s meaningful life sphere. Dignity as a meaningful life value is determined by the value of human and the assessment of its significance and place in society. The understanding of tolerance as a meaningful life value in family is highlighted, as the presence of tolerance directly affects the coexistence of adults and children in family, solves the question of how each family member can realize their rights towards such meaningful life values as freedom, dignity and love without limiting oneself and others. The tolerance in family creates conditions for the development of each family member, recognition of the right to create their own life and acceptance of their life choices. The pedagogical conditions of education of the adolescents’ meaningful life values in family are substantiated as the following: coordination of the adolescent’s meaningful life sphere, humanization of the educational environment of family, ethical mutual responsibility of family members, participation in training work. The practical significance of the article is that its materials can be used in organizing educational work of general education institutions, training of teachers, psychologists and pedagogical practice of students.